How We Can Locate Validatable Foundations of Life Themes - Jeremy Horne (Journal of Systemics, Cybernetics and Informatics)

(untitled)
Fractured personal identities contribute to conflict and corruption, underscoring the significance of comprehending identity, its expression, and societal context. Identity encompasses existence, fundamental values, and purpose, spanning from structured to arbitrary. Identity, itself, initiates one's core, which, in turn, produces virtues and ethics, molded by one's values. Living those values – internalizing them – is virtue. Imminent in our discourse is structure, repeatedly encountered in our journey through spacetime. Such bespeaks of order. We need to understand the nature of order and how it came to be, and implications for our identities. The Voris method, particularly the Authentic Life Theme Assessment (ALTA), is an identity proper, effectively demonstrating that one's core produces fundamental values that result in life themes, all affirming an individual's existence, distinctiveness, purpose, and influence.